Experimental analysis of reinforced concrete beams strengthened with steel bars and epoxy structural adhesive - Carvalho Silva, Ricardo José; Silveira Muniz, Mara Bruna; Feitosa Lima, Ésio Magalhães; Silva Júnior, Francisco Eudázio Suriano da; Araújo, Carlos Valbson dos Santos (Revista ALCONPAT, 2018)
This work was aimed at analyzing the efficiency of the strengthening of reinforced concrete beams with the addition of steel bars and epoxy adhesive. Five beams were produced, out of which four beams were strengthened to flexure. In two of them, “U” clips were also used to improve the anchorage of the strengthening. The tests demonstrated that the clips reduced the resistances of the beams compared to those without clips. The strengthened beams without clips yielded better results, but the largest limiting factor was the adherence between the epoxy and beam. The use of clips for solving the problem of adherence made this research original. The conclusions were based on the comparisons of the tested beams.